Mortality rates in pediatric septic shock - Desy Rusmawatiningtyas; Nurnaningsih Nurnaningsih (Paediatrica Indonesiana, 2016)
Background Septic shock remains a major cause of morbidity and mortality in children admitted to the intensive care unit. Recent investigations from developed countries have reported mortality rates of 20-30%. Few studies have reported mortality rates from pediatric septic shock in intensive care settings in developing countries with limited resources.  Objective  To determine the current mortality rates for pediatric patients with septic shock in a developing country.Methods A retrospective study was conducted in the Pediatric Intensive Care Unit (PICU) at DR. Sardjito General Hospital. Medical records and charts were reviewed and recorded for diagnoses of septic shock, from November 1st, 2011 to June 30th, 2014. Results  A database of all PICU admissions was assembled, and cases with diagnoses of septic shock were reviewed. The final data consisted of 136 patients diagnosed with septic shock. Septic shock was defined as a clinical suspicion of sepsis, manifested by hyperthermia or hypothermia, and accompanied by hypoperfusion  The overall mortality rate for the study cohort was 88.2%.  The median age of patients was 16 months, with 52.2% males. Median initial PRISM III and PELOD scores were 10 and 22, respectively. The median length of PICU stay was 4 days. A total of 48.5% of the subjects were in need of crystalloid and colloid fluid at a median amount of 40 mL/kg. The median time required to complete the initial resuscitation was 60 minutes. Mechanical ventilator support in the first 24 hours was required in 79.4% of the cases. Fluid overload of > 10% (FO>10%) was found in 58.8% of the subjects.Conclusion The mortality rate in pediatric septic shock in our hospital is very high. There is a higher incidence of fluid overload in the non-survival group .